LINGUISTIC MEANS OF CHARACTERIZATION OF THE PSYCHO-EMOTIONAL STATE OF A PERSON IN A LITERARY TEXT (ResearchJet Journal of Analysis and Inventions, 2021)
The article is devoted to the analysis of language means in the description of psychological state and emotional mood of personages of literary issues. Theoretical content of the article is proved by the extracts of literary books.